ANALISIS EFISIENSI BIAYA PRODUKSI DENGAN PENDEKATAN TARGET COSTING PADA PRODUKSI JENANG AYU DI UMKM JENANG AYU NITEN KECAMATAN WEDI KABUPATEN KLATEN, JAWA TENGAH - Wirawan, Nur Sahid (JURNAL ILMIAH AGRITAS, 2023)
The purpose of this study was to analyze the total production costs and production cost efficiency, analyze the comparison of the results of the calculation of production cost efficiency using the standard costing method and the target costing method and also analyze the effect of target costing on expected profits in UMKM Jenang Ayu Niten. The quantitative analysis method used is comparative descriptive which includes the standard costing method and target costing method and also uses simple linear regression analysis. Comparative descriptive analysis is carried out to compare the two methods so that it is known which method has a better efficiency level. Analysis using the target costing method was able to produce a higher net profit before PPH for MSMEs compared to the standard costing method with a difference of Rp 46,093,700 or equivalent to 11.86%. The level of cost efficiency after value engineering in UMKM Jenang Ayu Niten amounted to 61.79% and was better than before value engineering with a percentage difference of 1.02%. The value engineering is done by providing value added to product packaging in the form of standing pouch packaging with paper metal material so that it can increase the selling price and expected profit. After that, this study used a simple linear regression test with the results of the target costing variable (X) having a significant positive effect on expected profit (Y). The regression test results show that target costing has an influence of 94.6%. This proves that the effect of the target costing variable (X) on the expected profit variable (Y) is in the strong category and the remaining 5.4% is influenced by other variables not included in the research that has been done.